IDEDNIK syndrome: a newly recognized rare genetic disorder caused by AP1S1 and AP1B1 mutations - Wu, Rong; Luo, Xingguang; Wang, Xiao-Ping (Frontiers in Neurology, 2025)
IDEDNIK syndrome (formerly MEDNIK syndrome, OMIM #609313) is a rare autosomal recessive neurocutaneous disorder characterized by dysregulated copper metabolism and multisystem involvement. The primary causative gene, AP1S1, encodes the σ1A subunit of the adaptor protein complex AP-1, while mutations in AP1B1, encoding the β1 subunit, can cause a similar phenotype. Pathogenic mutations impair intracellular vesicle trafficking, disrupting the precise sorting and transport of multiple proteins, including the copper-transporting ATPases ATP7A and ATP7B. This results in defective copper homeostasis and a clinical phenotype overlapping features of Menkes and Wilson’s diseases. Hallmark manifestations include intellectual disability, enteropathy, deafness, peripheral neuropathy, ichthyosis, and keratoderma. Laboratory findings often reveal reduced serum copper and ceruloplasmin levels, with some patients exhibiting elevated hepatic or urinary copper. Cranial MRI typically demonstrates cerebral atrophy. No curative therapy is currently available; management is multidisciplinary, focusing on symptomatic relief and complication prevention. Oral zinc acetate has been reported to improve certain clinical features and biochemical parameters. This review provides a comprehensive update on the genetics, pathogenesis, clinical spectrum, diagnosis, management, and future directions for this debilitating disease.